Accessory REE mineralization of the Nokeng fluorite deposit as distal facies of the adjacent Vergenoeg pipe, Bushveld Complex, South Africa - Makhema, Relebohile Edward (University of the Witwatersrand, Johannesburg, 2024)
The Nokeng Plattekop deposit forms part of the Paleoproterozoic Bushveld Complex and it is located near Rust de Winter, approximately 80 km northeast of Pretoria. This deposit belongs to the Vergenoeg Igneous Complex, which is associated with a violent gas-vapour-rich rhyolitic eruption. The complex comprises the Vergenoeg discordant breccia pipe and a pyroclastic rock suite. Within the breccia pipe and associated pyroclastic rocks, rare earth element (REE) mineralization is observed in minerals like allanite, apatite, bastnasite, monazite, and xenotime. The Plattekop fluorite deposit, which lies 1000 m south of the breccia pipe, is postulated to represent spill-over remnants of the Vergenoeg volcanic edifice. This study performed a comprehensive petrographic and geochemical analysis of ore and pyroclastic breccia of the Nokeng Plattekop deposit, utilizing various analytical techniques, including optical microscopy, XRF, ICP-MS, and SEM. The aim is to characterise the style of accessory REE mineralization at Nokeng as a provisional distal facies of the Vergenoeg volcanic field. The findings of this study suggest that the Nokeng Plattekop deposit comprises a hematite-fluorite unit overlying an ignimbrite unit. Hematite-fluorite ores of the upper unit resemble the Vergenoeg ore, exhibiting elevated CaO concentrations and reduced SiO2 content attributed to high fluorite and hematite proportions. Conversely, the ignimbrite unit displays reduced CaO and elevated SiO2 concentrations, corresponding to lower fluorite content and higher rhyolitic lava fragments. The basal ignimbrite is proposed to have formed during the early stages of rhyolitic volcanism, while Nokeng and Vergenoeg ores formed during later stages dominated by Ca- and F-rich ferruginous magma. Petrographic evidence suggests hematite pseudomorphs after magnetite, indicating mineral assemblage evolution. REE mineralization in the Plattekop fluorite deposit is represented by bastnasite, monazite and xenotime, mostly associated with quartz, goethite, aegirine, hematite and fluorite. The highest REE + Y content (~ 5 890 ppm) is associated with Plattekop hematite-fluorite ores. Comparative analysis of REE distribution patterns suggests similar styles of mineralization between Vergenoeg and Nokeng, indicating both deposits as potential sources of REEs as by-product.
Research report submitted in partial fulfilment of the requirement for the degree of Master of Science in Economic Geology, to the Faculty of Science, School of Geoscience, at the University of the Witwatersrand, Johannesburg, 2024.
Keywords: Rare earth minerals; Plattekop; Nokeng fluorite mine; Vergenoeg fluorite mine; Bushveld igneous complex; Economic geology; UCTD; SDG-11: Sustainable cities and communities; SDG-15: Life on land